Association of low-grade inflammation caused by gut microbiota disturbances with osteoarthritis: A systematic review - Xiang, Wu; Ji, Bingjin; Jiang, Yiqin; Xiang, Han (Frontiers in Veterinary Science, 2022)
Background: Currently, many studies have been published on the relationship between the gut microbiome and knee osteoarthritis. However, the evidence for the association of gut microbiota with knee osteoarthritis has not been comprehensively evaluated. Objective: This review aimed to assess existing results and provide scientific evidence for the association of low-grade inflammation caused by gut microbiota disturbances with knee osteoarthritis. Methods: This study conducted an extensive review of the current literature using four databases, PubMed, EMBASE, Cochrane Library and Web of Science before 31 December 2021. Risk of bias was determined using ROBINS and SYRCLE, and quality of evidence was assessed using GRADE and CAMADARES criteria. Twelve articles were included. Results: Studies have shown that a high-fat diet leads to a disturbance of the gut microbiota, mainly manifested by an increase in the abundance of Firmicutes and Proteobacteria, a decrease in Bacteroidetes, and an increase in the Firmicutes/ Bacteroidetes ratio. Exercise can reverse the pattern of gain or loss caused by high fat. These changes are associated with elevated levels of serum lipopolysaccharide (LPS) and its binding proteins, as well as various inflammatory factors, leading to osteoarthritis (OA). Conclusion: This systematic review shows that a correlation between low-grade inflammation caused by gut microbiota disturbances and severity of knee osteoarthritis radiology and dysfunction. However, there was a very small number of studies that could be included in the review. Thus, further studies with large sample sizes are warranted to elucidate the association of low-grade inflammation caused by gut microbiota disturbances with osteoarthritis, and to explore the possible mechanisms for ameliorating osteoarthritis by modulating gut microbiota.